Urban "Heat-Island Effect" and its Connection with Architectural and Climatic Features on the Example of Poltava - Golik, Yuri; Illiash, Oksana; Maksiuta, Nataliia (International Journal of Engineering and Technology, 2018)
The concept of "heat-island effect", its structure and features of formation over the city are given. The climatic and other features of the city that influence the formation of this phenomenon are mentioned.Â The data on functioning in the city of the municipal production enterprise of the heat economy is indicated. The traditional method for determining the formation of the urban "heat-island effect" is described. The data and comparative graphs on the temperature regimes of the city and region are presented. The possibility of influencing architectural features of the city on the formation of the "heat-island-effect" is determined. According to the obtained results, further integrated researches are proposed for obtaining reliable results of the given question.Â